Psychological Factors Influencing Students' Anxiety in Speaking English - Yuliana, Rini; Haryanti, Ari Putri (Universitas Muhammadiyah Tangerang, 2024)
This study aimed to investigate the psychological factor influencing the students’ anxiety in speaking English. It used a descriptive qualitative approach. The data were acquired by using observation, open-ended questionnaires, and interviews. There were nine students in the second semester of ITB Adias Pemalang participating in this research. The data was analyzed through data reduction, display, and conclusion drawing established. The findings indicated that communication apprehension, test-anxiety, and fear of negative evaluation were three main factors causes of the students’ anxiety when speaking English. The findings of this research can be as a guide to examine the students’ anxiety during their studies in order to improve the students’ motivation and confidence when speaking the target language.